2004
DOI: 10.1002/app.13588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetonitrile pretreatment on the physicochemical behavior of 100% polyester fabric

Abstract: Acetonitrile pretreatment of 100% poly-(ethylene terephthalate) fabric was performed over different lengths of time. The influence of solvent treatment on the dyeing behavior and some of the physicochemical properties were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…This is also supported by the fact that the dye uptake of solvent pretreated fabric materials has improved because of development of voids. The observed results resemble those of earlier reports available in the literature [13,25].…”
Section: Scanning Electron Microscopy Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…This is also supported by the fact that the dye uptake of solvent pretreated fabric materials has improved because of development of voids. The observed results resemble those of earlier reports available in the literature [13,25].…”
Section: Scanning Electron Microscopy Studiessupporting
confidence: 92%
“…A very recent research work reported by Najafi et al [11] discussed the process of dyeing polyester/cotton fabrics using disperse/reactive dyestuff in one-bath dyeing process after coating the fabric with chitin biopolymer and then dyed with sulphato ethyl sulphonyl disperse/reactive dyes. Reports are available on the use of single solvent assisted dyeing of polyester and polyester/cotton blends [12][13][14]. Dystar Textilfarben GMBH & Co. has patented dyeing of polyester/cotton blends fabrics with disperse and reactive dyes in a one-bath process in alkaline medium using disperse dyes which are stable in alkaline medium [15].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the energy cost, more efficient processes, such as pretreatment with solvents, have been conceived as an effective route for producing atmospheric pressure dyeable polyester. Extensive research has been carried out on modifying polyesters with the use of solvents [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Researchers [2,12,13] have established that treatment of PET with a suitable solvent results in molecular rearrangement, giving a morphological structure to PET, such as to make it more dye receptive.…”
Section: Introductionmentioning
confidence: 99%
“…The process by which to produce low temperature dyeable PET with a methylene chloride pretreatment has been patented [15,16]. Solvent treatments did not have any adverse effects on the other properties of PET [3].…”
Section: Introductionmentioning
confidence: 99%
“…2 Work on the use of solvents for improved dyeing of polyester has been reported. [3][4][5][6][7][8][9][10] It has been reported that the pretreatment of fibers with various solvent systems can modify their physical structures in a way that they become presensitized to subsequent dyeing processes.…”
Section: Introductionmentioning
confidence: 99%